(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2023)
The Colombian educational system contemplates among its formative process numerical learning and the acquisition of skills in relation to mental calculation. That is why this reflection related to "Playful as a Pedagogical Strategy for the Strengthening of Numerical Thinking in Basic Elementary Students" is based on the experience that is lived in the San Francisco de Asís Archdiocesan Technical Institute, Santa Marta de Pamplona, in Norte de Santander, where shortcomings are observed in the strategies applied by some teachers for the teaching of mathematical content, evidencing the students when they choose the area of learning of your preference, by developing basic activities in a set time, in harmonious learning of the contents and the Saber tests that are developed at the different levels. This process causes research interest.